You are thinking, reflecting, analysing what you see and what you do all the time - Carlos Frederico Confort Campos; Nicolle Taissun (Sociedade Brasileira de Medicina de Família e Comunidade, 2024)
Introduction: Communication is recognized as a central skill by various international medical education regulatory bodies. Specific teaching on communication skills is important to enhance doctors' communication. Experiential techniques appear to be superior compared to traditional models. Real-life consultation helps trainees visualize their interview skills and reflect on them. Upgraded by technology, the use of video-recorded medical visits became the standard approach for communication teaching. However, the effectiveness pf this technique relies on trainees' active involvement. Their inputs and peer feedback on the recorded consultation are essential to learning. Despite its importance, their perspective on the usefulness of video feedback in medical education has received limited attention. Objective: To understand the perception of learning among general practice trainees as a result of the video feedback activity in their vocational training. Methods: An exploratory, qualitative study, conducted with first-year general practice trainees from an established training program in São Paulo, Brazil. Participants were interviewed after educational session, which were analyzed using reflexive thematic analysis. Results: Self-perception of their practice, communication skills learning, and affective gains were identified by participants as learning points derived from the video feedback activity. Furthermore, for specific communication skills learning, they mentioned nonverbal and verbal communication, theory and practice connections, consultation structure and opportunities for crystallizing knowledge. Affective gains included feeling part of a group, improving self-esteem, overcoming insecurities, perception of more effective consultations, reinforcing fondness for their work, and need for more learning. Conclusions: The learning gains identified in our study led to an experience of common humanity, which allowed participants to be more technically and affectively effective with their patients. Also, we identified that the video feedback educational activity can be used for other possible educational purposes, beyond the teaching of communication.